Constructing and Standardizing A Skill test Battery For Players of The National Center for Gifted in Handball - Amhed, Nawras; Drosh, Ammar (Journal of Physical Education, 2019)
The researchers noticed that most test batteries in the national center for gifted in handball do not live up to the requirements of the sport. Most test batteries depend on motor and physical abilities while clearly neglecting skill tests. Thus the researchers constructed a test battery for skill tests that consisted of four standardized tests.